2021
DOI: 10.3390/nano11113043
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ferroelectric, Dielectric Properties of Fe-Doped PMN-PT Thin Films

Abstract: Fe-doped 0.71Pb(Mg1/3Nb2/3)O3-0.29PbTiO3 (PMN-PT) thin films were grown in Pt/Ti/SiO2/Si substrate by a chemical solution deposition method. Effects of the annealing temperature and doping concentration on the crystallinity, microstructure, ferroelectric and dielectric properties of thin film were investigated. High (111) preferred orientation and density columnar structure were achieved in the 2% Fe-doped PMN-PT thin film annealed at 650 °C. The preferred orientation was transferred to a random orientation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Among the studies about Hf x Zr 1-x O 2 , the work in this study showed relatively good remanent polarization and fatigue endurance performances despite being under the lowest deposition temperature. Feng et al [ 2 ] focus their work on the effects of annealing temperature and Fe-doping concentration on the crystallinity, microstructure, ferroelectric and dielectric properties of PMN-PT thin films. 2% Fe-doped PMN-PT thin film annealed at 650 °C exhibits high (111) preferred orientation, high remanent polarization ( P r = 23.1 μC/cm 2 ) and low coercive voltage (Ec = 100 kV/cm).…”
mentioning
confidence: 99%
“…Among the studies about Hf x Zr 1-x O 2 , the work in this study showed relatively good remanent polarization and fatigue endurance performances despite being under the lowest deposition temperature. Feng et al [ 2 ] focus their work on the effects of annealing temperature and Fe-doping concentration on the crystallinity, microstructure, ferroelectric and dielectric properties of PMN-PT thin films. 2% Fe-doped PMN-PT thin film annealed at 650 °C exhibits high (111) preferred orientation, high remanent polarization ( P r = 23.1 μC/cm 2 ) and low coercive voltage (Ec = 100 kV/cm).…”
mentioning
confidence: 99%